Leading engagement of academic and clinical communities for learning : final report. - Creedy, Debra; Henderson, Amanda (Australian Learning and Teaching Council (ALTC), 2008)
Final report on the Leading Engagement of Academic and Clinical Communities for Learning project undertaken by Griffith University, Queensland Health, and three Queensland hospitals. The project aimed to develop an effective partnering model between universities and nursing clinical settings to improve clinical education. The model proposed a systematic approach to communication at a number of levels of leadership: university/hospital management, course convenors and nursing managers, and lecturers, clinical facilitators and students. The purpose of the project was enacting leadership [through clinical learning circles] that fostered communication and partnership between the academic and service sectors to improve undergraduate clinical learning experiences.